1985
DOI: 10.1111/j.1365-3040.1985.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme patterns in energy metabolism during flower induction in spinach leaves

Abstract: Abstract. Time series measurements of six enzymes linked to different pathways in energy metabolism [NAD- and NADP-dependent glyceraldchyde-3-phosphate dehydrogenase (NAD- and NADP-GPDs), adenylate kinase (AK), malate dehydrogenase (MDH), glucose-6-phosphate dehydrogenase (G-6PDH) and 6-phosphogluconate dehydrogenase (6-PGDH)] have been performed in spinach leaves subjected to different photoperiodic treatments, inductive or not of the flowering process. It is shown that the vegetative and the floral states ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…NAD-dependent glyceraldehyde-3-phosphate dehydrogenase; Bonzon 1985). For some enzymes this increase seemed to be specific for the flower-induced state, since it persisted even when the plants were transferred back to SD conditions.…”
Section: Discussionmentioning
confidence: 97%
“…NAD-dependent glyceraldehyde-3-phosphate dehydrogenase; Bonzon 1985). For some enzymes this increase seemed to be specific for the flower-induced state, since it persisted even when the plants were transferred back to SD conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Recent results show that photoperiodic flower induction is accompanied with changes in genome expression. Enzyme activities in the leaf of the long-day (LD) plant Spinacia oleracea show a different time course during the photoinductive cycle [3,13] and Kannangara et al [8] have analysed the polypeptides of the leaves of the short-day (SD) plant Xanthium strumarium and found that, at the end of the inductive long dark period, two polypeptides disappeared.…”
Section: Introductionmentioning
confidence: 99%